Atheroprone flow activates inflammation via endothelial ATP-dependent P2X7-p38 signalling. (6th November 2017) - Green, Jack P; Souilhol, Celine; Xanthis, Ioannis; Martinez-Campesino, Laura; Bowden, Neil P; Evans, Paul C; Wilson, Heather L
Abstract: Objective: Atherosclerosis is a focal disease occurring at arterial sites of disturbed blood flow that generates low oscillating shear stress. Endothelial inflammatory signalling is enhanced at sites of disturbed flow via mechanisms that are incompletely understood. The influence of disturbed flow on endothelial adenosine triphosphate (ATP) receptors and downstream signalling was assessed. Methods and results: Cultured human endothelial cells were exposed to atheroprotective (high uniform) or atheroprone (low oscillatory) shear stress for 72 h prior to assessment of ATP responses. Imaging of cells loaded with a calcium-sensitive fluorescent dye revealed that atheroprone flow enhanced extracellular calcium influx in response to 300 µM 2'(3')-O-(4-Benzoylbenzoyl) adenosine-5'-triphosphate. Pre-treatment with pharmacological inhibitors demonstrated that this process required purinergic P2X7 receptors. The mechanism involved altered expression of P2X7, which was induced by atheroprone flow conditions in cultured cells. Similarly, en face staining of the murine aorta revealed enriched P2X7 expression at an atheroprone site. Functional studies in cultured endothelial cells showed that atheroprone flow induced p38 phosphorylation and up-regulation of E-selectin and IL-8 secretion via a P2X7-dependent mechanism. Moreover, genetic deletion of P2X7 significantly reduced E-selectin at atheroprone regions of the murine aorta. Conclusions: These findings reveal that P2X7 is regulated by shear forces leading to its accumulation at atheroprone sites that are exposed to disturbed patterns of blood flow. P2X7 promotes endothelial inflammation at atheroprone sites by transducing ATP signals into p38 activation. Thus P2X7 integrates vascular mechanical responses with purinergic signalling to promote endothelial dysfunction and may provide an attractive potential therapeutic target to prevent or reduce atherosclerosis.